Cecilia Cârja, Ioana-Mihaela Bonda (coordonatori), Universitari și universități în spațiul românesc (secolele XIX–XX). Studii și interpretări [Academics and universities in the Romanian space (19th–20th Centuries). Studies and interpretations], Cluj-Napoca, Editura Mega, 2023, 161 p. - LUCA, Lorena (Studia Universitatis Babeș-Bolyai Historia, 2025)
Universities represent more than mere centres of intellectual formation. They are dynamic communities where academic traditions, human relationships, and professional trajectories intertwine, shaping the cultural identity of a society. The volume entitled Universitari și universități în spațiul românesc (secolele XIX–XX). Studii și interpretări brings together a series of scholarly contributions authored by various Romanian researchers united by a common interest in the history of Romanian higher education. Functioning as a thematic collection of studies, the book offers, through each chapter, distinct perspectives on the development of university institutions, as well as on the professional and intellectual trajectories of academic staff within the Romanian space throughout the 19th and 20th centuries. This volume emerged following the National Congress of Romanian Historians, held in Alba Iulia between 8–10 September 2022, which featured a section dedicated specifically to university history. In the aftermath of this event, the volume's coordinators, Cecilia Cârja and Ioana-Mihaela Bonda, archivists and historians within the Archives of the "Babeș-Bolyai" University, published six of the studies presented at the congress, acting not only as editors but also as contributors through their own studies.